STUDI PETROGRAFI BATUAN BEKU GUNUNG SINGA BOGOR - JAWA BARAT - -, Johanes Hutabarat; -, Mulyono (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
This research about study on petrography of igneous rocks (dacitic) of Gunung Singa, Nanggung, Bogor, West Java.Results of petrography and chemical analysis of these igneous rocks indicates that volcanics rock (lava) as dacite.Petrographic description of dacite show by porphyritic textures with plagioclase and pyroxene minerals as phenocryst. Mineralogical composition of these rocks consist of plagioclase, pyroxen, K-Felsdpar, amfibole, and opaque minerals, and secondary minerals like chlorite, clay minerals, epidote and opaque minerals.